Étudier l’argumentation selon la perspective francophone. Le cas du discours sur des questions juives - Pirogowska, Ewa (2023)
The author presents her current research project dealing with the argumentation of written interactions that appeared in cyberspace. They focus on the activities of the artist, humorist, political activist Dieudonné M’Bala M’Bala in France and, in Poland, around the activities of the journalist, philo-semitic performer Rafał Betlejewski. The common point of these discourses is that they trigger argumentative mechanisms that are part of the anti-Semitic attitudes of the interacting subjects. It demonstrates how the methodologies of French-speaking linguists can be useful for the argumentative analysis of such a difficult textual corpus.
Keywords: argumentative analysis; antisemitism; linguistic image of the world; corpus-based research; French linguistics